Numerical analysis of center cracked orthotropic fgm plate: Crack and material axes differ by ?o - Kaman, Mete Onur; Cetisli, Fatih (Techno-Press, 2012)
In this study, fracture analysis of orthotropic FGM (Functionally Graded Material) plate having center crack is performed, numerically. Material axis arbitrarily oriented and there is an angle theta(o) between material and crack axes. Stress intensity factors at the crack tips for Mode I are calculated using Displacement Correlation Method (DCM). In numerical analysis, effects of material properties and variation of angle theta(o) between material and crack axes on the fracture behavior are investigated for four different boundary conditions. Consequently, it is found that the effect of theta(o) on stress intensity factor depends on variation of material properties.
Keywords: orthotropic functionally graded materials; displacement correlation method; finite element analysis; stress intensity factor; aerospace structures